Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

How to solve equations of the form ax^4 + bx^2 +c = 0?

Can the quadratic equation be used to solve this equation

5 Answers

Relevance
  • 5 years ago

    Given: ax^4 + bx^2 +c = 0

    Let u = x^2.

    Substitute this variable u into the given equation.

    au^2 + bu + c = 0 --> quadratic equation in variable u.

    Then solve it the usual way like you do with quadratic equations.

    BUT remember that u = x^2 so once you've found u, you still need to take the square root to find x.

  • 5 years ago

    The trick here is to create another variable, say 'y', where y = x^2

    ax^4 + bx^2 + c = 0

    a(x^2)^2 + b(x^2) + c = 0

    a(y)^2 + b(y) + c = 0

    You are now left with a quadradic equation.

  • 5 years ago

    Let t = x² then you have at²+bt+c = 0 and the quadratic formula is readily applicable.

  • This is a special form of the quadratic. A quadratic equation can be more correctly defined as:

    a * f(x)^2 + b * f(x) + c = 0

    f(x) = (-b +/- sqrt(b^2 - 4ac)) / (2a)

    In this case, f(x) = x^2

    x^2 = (-b +/- sqrt(b^2 - 4ac)) / (2a)

    x = +/- sqrt((-b +/- sqrt(b^2 - 4ac)) / (2a))

  • How do you think about the answers? You can sign in to vote the answer.
  • DWRead
    Lv 7
    5 years ago

    This is EXACTLY the type of equation that is solved by the quadratic formula!

    x = [-b ± √(b²-4ac)] / (2a)

Still have questions? Get your answers by asking now.